Frequency and Reasons for Removal of Bone Plate Following Maxillofacial Surgery - Hussain, Mushahid; Uppal, Asma; Khan, Yahya; Siddique Ullah; Ammar, Muhammad; Bilal, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: In maxillofacial procedures, bone plates are frequently utilized for internal fixation. However, if they are there for an extended period of time, they may cause problems that require removal. Routine removal is still up for discussion despite improvements in materials and processes. Objective: to ascertain the clinical justifications and frequency of bone plate removal in a tertiary care context after maxillofacial surgery. Methods: In a tertiary care hospital Quetta, a six-month qualitative study was carried out from October 2024 to March 2025. A total of 120 patients who had bone plate fixation and removal were included in the study using random selection. Semi-structured interviews with an emphasis on patient experiences and clinical grounds for removal were used to gather data. Results: The majority of patients (65%) were between the ages of 31 and 45. The most often fractured location (53.3%) and plate-removal site (60%), respectively, was the mandible. Most of the plates were taken out between six and twelve months after they were first fixed. Infection (31.7%), plate exposure (21.7%), and pain/discomfort (18.3%) were the main causes of removal. Less often reported causes included mechanical failure and psychosocial problems. Conclusion: After maxillofacial surgery, infection, exposure, and discomfort frequently make bone plate removal necessary. The results highlight how crucial appropriate surgical technique, patient education, and customized postoperative care are. To lessen long-term issues, more investigation into bioresorbable materials and better fixation techniques is advised.